Ranchos Folclóricos na Nazaré: Permanências e Rupturas - Vaz, Margarida Leite de Almeida (2021)
FILME visualizável em https://drive.google.com/file/d/14jOrNlhaCozzoTGt19gb7stq0PNpREB/view?usp=sharing ou em https://www.youtube.com/watch?v=iyCarpT4CEE